Bringing the Military Back in Political Transition: A Response to Heo and Yun. (January 2015) - Kim, Insoo
In August 2012, Armed Forces & Society published an article by Insoo Kim, "Intra-military Divisions and Democratization in South Korea." Uk Heo and Seongyi Yun refuted Kim's argument in their Disputatio Sine Fine response, "Another View on the Relationship between Democratization and Intra-Military Division in South Korea, " published in April 2013. In the article, Heo and Yun argued that there was no clear sign of schism in the South Korea military and economic development substantially produced favorable condition for democratization in South Korea. Kim, by contrast, maintains that that the effect of intra-military division on political transition should be incorporated into the explanation of democratization in South Korea because Heo and Yun do not justify their claim that there was no clear evidence of schism in the South Korean military.